Penerapan Model Make A Match pada Pembelajaran Tematik Terpadu untuk Meningkatkan Hasil Belajar Siswa - Monli, Monalisa; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to determine the increase in learning outcomes after learning with the cooperative model make a match type. The research method uses Classroom Action Research with qualitative and quantitative approaches carried out in 2 cycles covering four stages, namely planning, implementing, observing and reflecting. The subjects of this study were teacher and 21 fourth grade students of SDN 15 Koto Tangah. The results showed that the succes in the first cycle lesson plan was 87,5% then increased in the second cycle to 94%. The success of observing theacher activity in cycle I was 68,75%, increasing in cycle ii 96,8%. While the increase in the activity of student aspects in the first cycle was 73,43% and the increase in the second cycle was 93,75%. The average learning outcomes in the knowledge aspect in the first cycle was 74,04, increasing in the second cycle to 84,29. While the average learning outcomes in the skills aspect in the first cycle was 76,96, increasing in the second cycle to 83,98.